Judge orders participants in Signal chat group blunder to preserve all messages - Lowell, Hugo (The Guardian, 2025)
Restraining order was issued to ensure that records of Yemen attack group conversation are retained
Keywords: CIA; Donald Trump; Marco Rubio; Pete Hegseth; Signal group chat leak; Trump administration; US national security; US news; US politics